LEVEL OF CUSTOMER SATISFACTION BETWEEN SBI AND PRIVATE BANKS IN KRISHNAGIRI DISTRICT, TAMILNADU, INDIA - R. Muralidharan; Dr. D. Suthamathi (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Indian banking can be broadly categorized into nationalized banks (government owned), private banks and specialized banking institutions. The private sector banks continue to enjoy formidable customer’s confidence, goodwill and reputation as well as friendliness that have been created significantly in the rural and semi-urban areas. The strengths of a modern-day private bank are product innovation, diversification and optimum use of Information Technology, high level of capitalization, customers focus, less Non Performing Assets and higher profit growth and a team of specialized and highly motivated personnel.